A case of multiple trichilemmal cysts and a solitary proliferating trichilemmal tumor on the scalp - (:unkn) unknown (SPRINGER, 1997)
A case of multiple trichilemmal cysts of the scalp, one of which was a proliferating trichilemmal tumor, is presented. The nomenclature and pathology of these lesions is discussed.
Keywords: pilar; trichilemmal; cyst; tumor; PILAR TUMORS